أثر الركود الاقتصادي على الاعتمادات المستندية: دراسة حالة البنوك المصرية خلال (2012-2013) (El-Wahat Journal for Research and Studies, 2015)
Administration of letters of credit in the Egyptian Banks was suffered from a strong recession, during the period (2012-2013) because of rising US dollar against the Egyptian pound, which has increased fears of investors and importers, of imported products and high commodity prices, which is rejected by the Egyptian market during this period that suffer of strong recession at the economic level and at the level of the monthly income of the Egyptian citizen.  Moreover, political tensions in Egypt have led during that period to increase the decline of demand for import operations until the clarity of the political vision for Egypt. The reduction of Egypt's credit rating the local economy by Standard & Poor's to -B negative long-term perspective, to deepen the wounds of Activity letters of credits to banks, which suffered from the fluctuation of foreign exchange rates against the pound and the decline in business problems. Key words: Economic Recession, Letters of Credit, Egyptian